Cardiac ATP-Sensitive Potassium Channels: A Potential Target for an Anti-Ischaemic Pharmacological Strategy - Testai, L.; Rapposelli, S.; Calderone, V. (Cardiovascular & Hematological Agents in Medicinal Chemistry, 2007)
Brief periods of ischaemia induce in the myocardium an increased resistance to the injury due to a subsequent, more prolonged ischaemic episode. This phenomenon, known as ischaemic pre-conditioning (IPC), articulated in two distinct phases (an early and a delayed one), is ensured by different biological mechanisms. Although an exhaustive comprehension of these mechanisms has not yet been reached, it is widely accepted that among the various signals involved as triggers and/or end-effectors, an important role is undoubtedly played by the activation of cardiac ATP-sensitive potassium channels (KATP). In the myocardial cells, KATP channels have been identified both in the sarcolemmal membrane (sarc-KATP) and in the mitochondrial inner membrane (mito-KATP). Although many experimental findings suggest that a role of sarc-KATP channel activation in IPC cannot be excluded, in the last few years, many authors have indicated that this phenomenon could be attributed to the exclusive (or at least prevalent) activation of the mito-KATP channels. Conversely, drugs modulating the KATP channels (as activators or blockers), on one hand, have been employed as useful experimental tools for basic studies on IPC. On the other hand, KATP-openers have been viewed as promising possible therapeutic agents for limiting the myocardial injury due to ischaemic episodes. In particular, those molecules exhibiting a good degree of selectivity towards the mito-KATP channels have been indicated as potential anti-ischaemic cardio-protective pharmacological tools, devoid of other biological effects (such as negative inotropic activity, hypotension or hyperglycaemia) linked to the activation of cardiac and non-cardiac sarcKATP channels. In this paper, we wish to report the experimental evidence supporting the role of sarc- and mito-KATP channels in IPC, the relative signalling pathways potentially involved in the mechanisms of cardio-protection and, finally, an overview of the most important molecules acting as activators or blockers of KATP channels, with their selectivity profiles.
Keywords: reactive oxygen species